Slittable sheath supported right ventricular pacing lead implantation in persistent left superior vena cava with absent right superior vena cava: a case report - Plášek, Jiří; Vrtal, Jiří; Šipula, David; Grézl, Tomáš; Václavík, Jan (Journal of medical case reports, 2023)
BACKGROUND: Persistent left superior vena cava (PLSVC) is the most common variant of systemic venous drainage. In the absence of the right superior vena cava (RSVC), implantation of a right ventricular pacing lead may be challenging. Therefore specific implantation techniques and experiences in PLSVC are worth reporting. CASE PRESENTATION: We present a case report of a 90-year-old Caucasian female patient with PLSVC during single chamber pacemaker implantation due to the third-degree atrioventricular block. With common implantation techniques, we did not even reach the right ventricle. Therefore slittable CPS Direct TM Universal sheath was employed to overcome the acute angle from PLSVC to tricuspid valve and ensure more fixation stability for longer 100-cm right ventricular lead placement. CONCLUSION: This case demonstrates safe implantation of 100-cm long right ventricular bipolar active fixation pacing lead using common slittable CPS Direct TM Universal sheath after failed attempts with "C" and "J" stylet shaped electrode. This sheath provides different angle towards tricuspid valve and more fixation stability in patient with PLSVC and absent connection to right atrium.
Keywords: Female; Heart Ventricles; senioři nad 80 let; kardiostimulátor; Humans; srdeční komory; Aged, 80 and over; Persistent Left Superior Vena Cava; perzistující levostranná vena cava superior; Vena Cava, Superior; Atrioventricular Block; Pacemaker, Artificial; ženské pohlaví; vena cava superior; atrioventrikulární blokáda; lidé